Placenta-specific 8 is overexpressed and regulates cell proliferation in low-grade human pancreatic neuroendocrine tumors - Tatura, Marina; Schmidt, Harald; Haijat, Mikail; Stark, Maren; Rinke, Anja; Diels, Ramon; Lawlor, Rita T.; Scarpa, Aldo; Schrader, Jörg; Hackert, Thilo; Schimmack, Simon; Gress, Thomas Mathias; et al. (Neuroendocrinology, 2020)
Background/Aims: Many aspects of the biology of pancreatic neuroendocrine tumors (PanNETs), including determinants of proliferative, invasive, and metastatic potential, remain poorly understood. Placenta-specific 8 (PLAC8), a gene with unknown molecular function, has been reported to have tumor-promoting roles in different human malignancies, including exocrine pancreatic cancer. Since preliminary data suggested deregulation of PLAC8 expression in PanNET, we have performed detailed analyses of PLAC8 expression and function in human PanNET. Methods: Primary tissue from PanNET patients was immunohistochemically stained for PLAC8, and expression was correlated with clinicopathological data. In vitro, PLAC8 expression was inhibited by siRNA transfection in PanNET cell lines and effects were analyzed by qRT-PCR, Western blot, and proliferation assays. Results: We report that PLAC8 is expressed in the majority of well-differentiated human PanNETs, predominantly in early-stage and low-grade tumors. SiRNA-mediated knockdown of PLAC8 in PanNET cells resulted in decreased proliferation and viability, while apoptosis was not induced. Mechanistically, these effects were mediated by attenuation of cell cycle progression, as Western blot analyses demonstrated upregulation of the tumor suppressor p21/CDKN2A and downregulation of the cell cycle regulator Cyclin D1 as well as reduced levels of phosphorylated ribosomal protein s6 and retinoblastoma protein. Conclusion: Our findings establish PLAC8 as a central mediator of cell growth in a subset of human PanNET, providing evidence for the existence of distinct molecular subtypes within this class of tumors.
Gesehen am 18.02.2020